Reading Home Cultures Through Books - Salmi-Niklander, Kirsti; Dalbello, Marija (Taylor & Francis, 2022)
This wide-ranging, comparative, and multidisciplinary collection addresses the significance of books in creating the idea of home. The chapters present cases that reveal the affective and sensory dimensions of books and reading in the practice of everyday life of individuals, in communities, and in society. The complex relationship of books, reading, and home is explored through American and European case studies both in bourgeois and middle-class homes, and in working-class and immigrant families and communities with limited possibilities for reading. The volume combines the conceptions and representations of domesticity, the materiality of reading, and library as a place, drawing on book history and material culture studies as well as anthropology and sociology of the home.